Analisis Pengaruh Lingkungan Kerja dan Iklim Organisasi terhadap Kolaborasi Pegawai yang Dimediasi Variabel Budaya Kerja pada Departemen Pengelolaan Uang - Riky Wahyu Kurniadi; Lies Putriana; Seta A Wicaksana (Jurnal Syntax Admiration, 2025)
This study aims to analyze the influence of the work environment and organizational climate on employee collaboration, with work culture as a mediating variable at the Currency Management Department of Bank Indonesia. A quantitative approach was applied, and data were analyzed using Partial Least Square (PLS). The results indicate that the work environment and organizational climate have a significant positive effect on work culture. Furthermore, the organizational climate significantly affects employee collaboration, while the work environment does not have a direct significant impact. Work culture plays a crucial role as a mediator, strengthening the relationship between the work environment and organizational climate on employee collaboration. This study emphasizes the importance of fostering a supportive work culture to enhance collaboration within organizations.